PELAKSANAAN OUTSOURCING PADA PT. ANDIKA PRATAMA ABADI DITINJAU DARI HUKUM PERDATA DAN UNDANG – UNDANG KETENAGAKERJAAN - Suhatrizal Suhatrizal; Amran B (Universitas Medan Area, 2014)
Essentially outsourcing implementation interconnected with practict ofwork, so a lot of regulations that related with workship be essent factor inmotivation outsourcing development in Indonesia. Legalisation in usingoutsourcing service in still younger in 2003, when the legislation born. It mean acompany can give a most implementation of working to other company withagreement of working contracting or with supplying of workers merit that donewrited, and it was called sub contract.